2011
DOI: 10.1111/j.1365-2133.2011.10482.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased retinol‐binding protein (RBP) 4 and anti‐RBP4 antibody in alopecia areata

Abstract: Our data demonstrate that AA is associated with increased serum levels of RBP4 and positive IgG immunoreactivity against recombinant human RBP4. These results suggest that the major components for the retinoic acid biosynthesis pathway may be crucially involved in the pathogenic process of AA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Ahn et al demonstrated that AA is associated with increased serum levels of RBP4 and positive IgG immunoreactivity against recombinant human RBP4. These results suggested that the major components for the RA biosynthesis pathway may be crucially involved in the pathogenic process of AA …”
Section: Discussionmentioning
confidence: 88%
“…Ahn et al demonstrated that AA is associated with increased serum levels of RBP4 and positive IgG immunoreactivity against recombinant human RBP4. These results suggested that the major components for the RA biosynthesis pathway may be crucially involved in the pathogenic process of AA …”
Section: Discussionmentioning
confidence: 88%